ANALYSIS OF FACTORS INFLUENCING ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB): A CASE STUDY OF KINDERGARTEN TEACHERS IN BEKASI CITY - Griet Helena Laihad; Eka Suhardi (Universitas Indraprasta PGRI, 2023)
In childhood, when all of a child's functions and abilities are rapidly developing, it is the responsibility of adults to offer the proper stimulation so that their abilities can be optimally realized and developed. This emphasizes the significance of teaching staff/professional teachers in personality and social concerns, in addition to their pedagogy-related responsibilities. Thus, there is a demand for educators with organizational citizenship behavior (OCB). The purpose of this study is to investigate the factors that influence Organizational Citizenship Behavior (OCB) using a Case Study of 175 Kindergarten Teachers in Bekasi City. Organizational culture, leadership style, and decision making are the contributing elements. This study employs a quantitative methodology and path analysis techniques. (1) According to the study's findings, organizational culture has a direct influence on the organizational citizenship behavior of preschool teachers. (2) Leadership style influences directly the citizenship behavior of preschool teacher groups. (3) Decision-making has an immediate impact on the citizenship behavior of preschool teacher organizations. (4) The corporate culture has a direct impact on the decision-making process (5) The leadership style has a direct impact on the decision-making process. In order to improve the organizational citizenship behavior of preschool teachers, organizational culture, leadership style, and decision-making must be examined